Respuesta :

1uxwl

2(6-5x)+11=43

12-10x+11=43

23-10x=43

-10x=20

x=-2

x=-2.  

First you subtract by eleven from both sides of equation form. And it gave us, [tex]2(6-5x)+11-11=43-11[/tex]. Then you simplify by the equation, and it gave us, [tex]2(6-5x)=32[/tex]. Next, you had divide by two from both sides of equation form. And it gave us, [tex]\frac{2(6-5x)}{2}=\frac{32}{2}[/tex]. And then you simplify by the equation, and it gave us, [tex]6-5x=16[/tex]. Next, you had subtract by six from both sides of equation form. And it gave us, [tex]6-5x-6=16-6[/tex]. And then you simplify by the equation, and it gave us,[tex]-5x=10[/tex]. Next, you had divide by negative five from both sides of equation form. And it gave us, [tex]\frac{-5x}{-5}=\frac{10}{-5}[/tex]. And finally, you had simplify by the final answer and it gave us the final answer is, x=-2 is the final answer.   Hope this helps! And thank you for posting your question at here on brainly, and have a great day. -Charlie